Comparing the Effect of Face-To-Face Education and E-learning on the Physical Activity of the Elderly - Shahab Papi; Yadollah Abolfathi Momtaz; Mahshid Foroughan; Farahnaz Mohammadi Shahboulaghi; Marzieh Araban; Tahereh Ramezani (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Regular physical activity is very effective in preventing or delaying chronic diseases and premature death in the elderly. Objective: This study aimed to compare the effect of face-to-face education and e-learning methods on the physical activity of the elderly. Materials and Methods: This is a quasi-experimental study conducted in Karaj, Iran in 2018. The participants were 88 elderly people referred to a senior rehab center and then were assigned into three groups of face-to-face education (n=30), e-learning (n=28), and control (n=30).The study data were collected by a demographic form and the 41-item community healthy activities program for seniors questionnaire (CHAMPS) before the intervention, 1 month after the intervention, and 3-month follow-up. Face-to-face education and e-learning were presented to the two educational groups’ during eight 20-minute sessions. The obtained data were analyzed using ANOVA, Bonferroni post hoc test, the Chi-square test, and repeated measures ANOVA. The significance level was set at0.05. Results: Between the two educational groups, a significant difference was observed in the mean score of physical activity at three measurement phases (P = 0.001).The effect size was 0.61 for face-to-face education and 0.64 for e-learning. Based on the results of the Bonferroni post hoc test, there was no significant difference between e-learning and face-to-face education groups. Conclusion: Both face-to-face and e-learning methods were effective in promoting the physical activity behavior of the elderly. E-learning method can be used as one of the complementary methods of traditional education for improving the physical activity of the elderly.